A Photoluminescence Study of Dy3+ Emissions in Zircon from Central Highlands of Vietnam - Vương, Bùi Thị Sinh; Hương, Lê Thị Thu (VNU Journal of Science: Earth and Environmental Sciences; Vol 31 No 4, 2015)
It has been known that among REEs, Dy 3+ plays an important role in the structure of Zircon though it just exists as trace elements. The Dy 3+ is structured in the zircon crystalline lattice and it has a good fluorescent response. From all significant roles of this ion, this paper focused on clarifying the luminescence of Dy 3+ in Zircon from a mine in Central Highlands of Vietnam (Krong Nang, Dak Lak province) by Photoluminescence (PL) spectroscopy, Energy Dispersive spectrometer (EDS). The analytical results of EDS identified the presence of trace quantities of Dy 3+ in the bulk of zircon by the typical peaks. The PL spectra showed Dy 3+ emissions at some characterized band positions with the strongest band at 481nm (near 20790 cm -1 ) and  581 nm (near 17203 cm -1 ). The intensity of Dy 3+ emissions from zircon is related to the concentrations of this ion and its color; the higher the concentration of Dy 3+ , the higher the emission intensity and the brighter the color. The band width of the main peak of Dy 3+ emissions is narrow indicating that the zircon structure is well crystalline. Keywords : Zircon, Dy 3+ , Photoluminescence (PL) spectroscopy, Energy Dispersive spectrometer (EDS), Rare earth elements (REEs).